Riding on the frontier's crest : Mahican Indian culture and culture change - Brasser, Ted J. (Book collections on Project MUSE., 1974)
Detailed summary of the history and changing culture of the Mahican Indians, originally inhabiting the Hudson valley in New York State and closely interrelated with neighboring Iroquois confederacy.